2022
DOI: 10.3934/ipi.2021059
|View full text |Cite
|
Sign up to set email alerts
|

Joint reconstruction and low-rank decomposition for dynamic inverse problems

Abstract: <p style='text-indent:20px;'>A primary interest in dynamic inverse problems is to identify the underlying temporal behaviour of the system from outside measurements. In this work, we consider the case, where the target can be represented by a decomposition of spatial and temporal basis functions and hence can be efficiently represented by a low-rank decomposition. We then propose a joint reconstruction and low-rank decomposition method based on the Nonnegative Matrix Factorisation to obtain the unknown f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the feature fusion layer, the feature vector y1 is obtained from the nonlinear model. It is spliced with the feature vector y2 obtained from the linear model to form a fusion vector (15) Where represents the vector splicing operation. The feature vector contains both nonlinear features and linear features.…”
Section: Detail Of Fu Ntc Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the feature fusion layer, the feature vector y1 is obtained from the nonlinear model. It is spliced with the feature vector y2 obtained from the linear model to form a fusion vector (15) Where represents the vector splicing operation. The feature vector contains both nonlinear features and linear features.…”
Section: Detail Of Fu Ntc Modelmentioning
confidence: 99%
“…The fixed-point extension and approximate singular value decomposition algorithm for solving the rank minimization problem of large-scale matrices [12] proposed by Qiao et al Ahn et al Provide a boundary for the number of elements needed to reconstruct a low-rank matrix. It is optimal in the range of a small numerical constant and a logarithmic factor [13][14][15]. In addition, some studies have shown that, under certain constraints, the minimum kernel norm can be filled by partial observation elements of the matrix [16].…”
Section: Introductionmentioning
confidence: 99%
“…the object is to be reconstructed at a range of time points. Here, one usually has to deal with sparse data or limited angle problems [2,8,9]. Including motion, the Radon transform is now computed for a deformed version of ϑ over the whole time interval, which changes the setting to…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in medical imaging the CT image might be used for identification and quantification of cancer tissue [11]. Thus, in recent years some researchers have also increasingly considered to combine both tasks in a joint framework [12], [13], [14]. Nevertheless, we will concentrate here on a separated approach, but keep the segmentation quality in mind as evaluation criterion of reconstruction quality rather than quantitative reconstruction errors.…”
Section: Introductionmentioning
confidence: 99%